Total hip arthroplasty in ankylosing spondylitis in a tertiary care hospital: a prospective COHORT study - Pervez Ahsan; Israt Jahan; Abul Khair (International Journal of Research in Orthopaedics, 2023)
Background: Ankylosing spondylitis is a chronic inflammatory-type arthritis that forms part of the group of spondyloarthritides. It primarily affects the spine and pelvis but peripheral arthritis and enthesitis are also common features. Onset of AS often occurs at a relatively young age and that is accepted as a greater risk of hip involvement. THA in AS patients is a challenging procedure owing to multiple factors. The aim of this study was to evaluate the clinical, radiological & functional outcomes of total hip arthroplasty among patients with Ankylosing Spondylitis. Methods: This was a prospective cohort study and was conducted in the Department of Orthopaedic Surgery of Ibn Sina Medical College Hospital, Dhaka, Bangladesh during the period from June, 2021 to May, 2022. In this study we included fifty patients with ankylosing spondylitis who underwent total hip arthroplasty. Result: In our study we found the highest prevalence (36%) was present in aged between 31-40 years old. The mean±SD of age among patients was (37±12). We found the mean±SD of Harris hip score was 44.2±12.3 & 87.2±17.4 during preoperative & postoperative phase respectively. Conclusions: In our study, we found that total hip arthroplasty is a safe and effective treatment of advanced hip involvement in patients with AS. It results in significant improvements in objective outcome measures such as HHS, patient mobility & reduced the difficulty level of patients in their day-to-day activities.